SOCIO-ECONOMIC PREREQUISITES OF MULTICULTURAL EDUCATIONAL SYSTEM FORMATION IN THE FEDERATIVE REPUBLIC OF GERMANY - Kovalynska, Inna V. (Educological discourse, 2016)
The article deals with a description of socio-economic prerequisites that were the basis for multicultural educational system formation in the Federative Republic of Germany. The author considers West European countries from the point of view of the principle of multiculturalism implementation and thus classifies the countries into several groups, countries of labour migration in particular. The Federative Republic of Germany belongs to this group. A historic retrospective of the migration processes is presented in the article. The author substantiates the give classification of countries by providing statistical data about language, national, religious and demographic diversity in the country, and also the data about the quantity of migrants in the country within the last decade. In conclusion the author generalizes tendencies of socio-cultural  development of the country  and states that the Federative Republic of Germany aims at integration of nations, and this corresponds to the strategy of European identity formation.